Development of inland fisheries under constraints from other uses of land and water resources : - Dunn, I.G. (FAO, 1989)
Its purpose is to assist in reaching correct decisions in discussions between various specialist during planning, design, implementation and management phases of major river basin development projects with fisheries potential.